Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Kelas IV Di SDN 38 Kota Bengkulu - Ripito, Ade; Dewi, Citra; Perdima, Feby Elra (Journal Of Dehasen Educational Review, 2024)
This study aims to determine the implementation of learning physical education sports and health class iv at SDN 38 Bengkulu city. This type of research is descriptive qualitative with interview and documentation methods consisting of research informants from the principal, PJOK teacher, other subject teachers and students. The results showed that the implementation of class IV learning at SDN 38 Bengkulu City was good as evidenced by the preparation that had been prepared from home such as items that were needed but at school did not exist, and at one time the corner teacher also utilised existing items at school such as drinking bottles used as cardboard kun as kun and student jumping equipment. In the implementation stage the corner teacher can control the students and after finishing the corner teacher leads the cooling down and evaluates what to do and the improvement of the movements that must be done and gives assignments and returns the tools used to their place again. In other words, the class IV corner teacher at SDN 38 Bengkulu City has carried out learning activities well where the teachers have conditioned the interaction between students and their environment so that there is a change in behaviour towards the better.